KERJA SAMA KEPOLISIAN REPUBLIK INDONESIA (POLRI) DAN AUSTRALIAN FEDERAL POLICE (AFP) DALAM PENANGANAN ISU PENCARI SUAKA DAN PENYELUNDUPAN MANUSIA TAHUN 2008-2014 - Akbar Zudane (2023)
This research examines the role of cooperation between the Indonesian National Police (POLRI) and the Australian Federal Police (AFP) in addressing the issues of asylum seekers and people smuggling prevalent in Indonesia from 2008 to 2014. The research employs three approaches, namely the non-traditional security concept, security cooperation concept, and bilateral cooperation concept, to analyze the collaborative efforts in tackling the issues of asylum seekers and people smuggling. The research methodology employed in this study involves the utilization of qualitative descriptive analysis. The findings of this research indicate that the issues of asylum seekers and people smuggling have become significant challenges faced by the governments of Indonesia and Australia. Recognizing the limitations of a single country's ability to resolve these issues, cooperation between the two nations has become crucial.